Kepastian Hukum Pendaftaran Peralihan Hak Atas Tanah Saat Menjadi Objek Sengketa di Pengadilan (Studi Kasus Pelaksanaan Eksekusi terhadap Objek Perkara Perdata No. 18/Pdt.G/2018/PN Kbr) - Abdi, Israr; Mirwati, Yulia; Fendri, Azmi (UNES Law Review, 2024)
This research aims to examine and analyze the legal certainty of registering the transfer of land rights when it is the object of a dispute in court and to determine the legal consequences for land rights that have been transferred in the implementation of the Koto Baru District Court Decision No. 18/Pdt.G/2018/PN Kbr. This research uses empirical juridical methods, namely research carried out directly in the field to find out the actual problems that occur, then it will be connected to applicable laws and regulations and existing legal theories. The data collected is in the form of primary data and secondary data. Based on the research results, in the event that Land Rights are the object of a dispute in court, the case registration is automatically deleted within 30 (thirty) days from the date of recording and if there is a status quo order it is also automatically deleted within 30 (thirty) days. day. After the period for recording the object of the court case and/or the record of the object of determining the status quo as intended is deleted and the object of the case is not followed by a determination of collateral confiscation, the registration of the transfer or encumbrance of rights can be carried out. The Court's decision which has permanent legal force (In kracht van gewijsde) is considered correct and in this decision it is punitive (Condemnatoir) control/ownership of the land the object of execution is binding on the third party because obtaining rights to the land from the losing party (Defendant) occurred after If there is a case/case decision then the object of the case can be executed.